Assessment of the laser beam welding of galvanized car body steel with an additional organic protective layer - Górka, Jacek; Suder, Wojciech; Kciuk, Monika; Stano, Sebastian (MDPI, 2023)
This study discusses the effect of laser beam welding parameters on the structure, mechanical properties and corrosion resistance of 1.2 mm thick galvanized sheets made of low-carbon steel DC04 provided with a ZE36/36 GardoprotectOC2BU organic coating. The test laser beam butt welded joints were made without the filler metal, using a variable welding rate, where linear welding energy was restricted within the range of 30 J/mm to 90 J/mm. The joints were subjected to non-destructive tests, destructive tests and corrosion resistance tests. The tests revealed the possibility of making joints meeting the criteria specified in the ISO 15614-11 standard. Regardless of the value of linear welding energy applied in the process, all the joints were characterised by high mechanical and plastic properties. It was noticed that an increase in linear welding energy from 30 J/mm to 90 J/mm was accompanied by the widening of the weld and that of the heat-affected zone (HAZ). In addition, an increase in linear welding energy was accompanied by a decrease in the maximum weld hardness to approximately 250 HV0.2. In the HAZ, hardness was restricted within the range of 190 HV0.2 to 230 HV0.2 and decreased along with increasing linear welding energy. In the static tensile test, regardless of the value of linear welding energy, the test specimen ruptured in the base material. In the bend test, regardless of the value of linear welding energy, a bend angle of 180° was obtained without partial tear or scratches; unit elongation was restricted within the range of 29% to 42%. The electrochemical tests and experiments performed in the salt spray chamber revealed the very high effectiveness of the corrosion protections against aggressive chloride ions.
Keywords: car body sheets; laser beam welding; linear welding energy; mechanical properties; corrosion resistance